The Role of Early Childhood Teachers in Nurturing Grit and Perseverance In Preschool Children - Laumka, Runglawan; Sriwapee, Kanokwan; Wangsitthidet, Shuchada; Poowanna, Bongkotrat (Journal of Education Rajabhat Maha Sarakham University, 2024)
This article aims to provide teachers with knowledge, understanding, practical skills, and a positive perspective on fostering grit in preschool children (ages 3-6). It also presents examples of related research on grit as a guideline for teachers to adapt in child development. Grit is crucial for building a strong foundation for lifelong success as it demonstrates mental resilience, flexibility, problem-solving skills, self-confidence, a growth mindset, and discipline. These qualities form a robust foundation for academic success and quality of life in the future. Instilling grit in preschool children enables them to stand firm and strive against obstacles, being able to face challenges or failures and bounce back with resilience. Grit therefore essential and should be cultivated from an early age. The theoretical framework for fostering grit in preschool children includes the ecological systems theory of human development, cognitive development theory, and attachment theory. Teachers play a key role in building grit in preschool children through 1) creating a learning environment with diverse and challenging experiences, 2) building positive relationships, 3) using open-ended questions, 4) fostering a growth mindset, 5) encouraging children to face challenges, 6) assessment, 7) collaborating with parents, and 8) being a good role model.